Self-assembled amorphous drug–polyelectrolyte nanoparticle complex with enhanced dissolution rate and saturation solubility - Cheow, Wean Sin (2013)
The dissolution rate and solubility of poorly soluble drugs can be enhanced by formulating them into stable amorphous nanoparticle complex (nanoplex). For this purpose, a highly sustainable self-assembly drug–polyelectrolyte complexation process is developed, with ciprofloxacin and dextran sulfate as the drug and polyelectrolyte models, respectively. The nanoplex are prepared by mixing two aqueous salt solutions – one containing the drug and the other containing the oppositely charged polyelectrolyte. The nanoplex suspension is transformed into stable dry-powder form by freeze-drying. The effects of drug concentration, drug-to-polyelectrolyte charge ratio, and salt concentration on the complexation efficiency, yield, drug loading, and nanoplex morphology are examined. The dissolution rates and solubility of the nanoplex are characterized and compared to raw drug crystals. Nearly spherical amorphous nanoplex having fairly uniform sizes in the range of 200−400 nm and 80% drug loading are successfully produced at ⩾80% complexation efficiency and yield. The complexation efficiency is governed by the drug concentration and its ratio to the salt concentration. The nanoplex powders exhibit approximately twice higher dissolution rate and solubility than raw drug crystals and remain stable after one-month storage. Overall, amorphous nanoplex represent a promising bioavailability-enhanced formulation of poorly soluble drugs owed to their superior characteristics and ease of preparation.